Analisis Implementasi Pemungutan Pajak Bumi dan Bangunan (PBB) dan Dampaknya terhadap Pendapatan Asli Daerah - Eva Assalitsa Sabilla; Muhammad Zikri Assidik; Titi Rahayu (Jurnal Pajak dan Analisis Ekonomi Syariah, 2026)
This study aims to analyze the implementation of Land and Building Tax (Pajak Bumi dan Bangunan or PBB) collection and its significant impact on local revenue generation. Land and building tax is a crucial component of local government revenue in Indonesia, especially following the implementation of regional autonomy and fiscal decentralization policies. Despite its critical role in funding local infrastructure and public services, the realization of PBB often falls short of its potential targets. This research utilizes a qualitative descriptive approach, employing secondary data collected from local revenue agencies and extensive literature reviews of previous academic publications. The objectives are to evaluate the effectiveness of current collection mechanisms, identify the primary obstacles hindering taxpayer compliance, and assess the overall contribution of PBB to regional financial independence. The findings reveal that while the administrative framework for PBB collection is generally well-established, practical implementation faces numerous challenges, including outdated land value assessments, low taxpayer awareness, suboptimal database management, and limited human resources within the tax apparatus. Furthermore, the study indicates that targeted digitalization of tax services and proactive public socialization campaigns can significantly enhance compliance rates. Practically, the results provide valuable recommendations for local policymakers to reform their tax collection strategies, optimize revenue streams, and ensure sustainable regional development.